1999
DOI: 10.1094/cchem.1999.76.1.164
|View full text |Cite
|
Sign up to set email alerts
|

SDS‐Protein Gel Test for Prediction of Bread Loaf Volume

Abstract: Cereal Chem. 76(1): [164][165][166][167][168][169][170][171][172] Flour dispersed in aqueous solutions of sodium dodecyl sulfate (SDS) forms a proteinaceous gel when centrifuged at high speed. The conventional methodology for SDS gel testing was modified to develop a smallscale (<1 g of flour or wheat meal) screening test for evaluation of the protein quality of wheat for breadmaking. The principal modification involved centrifugation with a swinging-bucket rotor to facilitate direct measurement of gel height,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 16 publications
0
11
0
1
Order By: Relevance
“…Previous reports have agreed that GMP quantity is an indicator of wheat fl our quality (Weegels et al, 1996) and that the rigidity of the GMP gel layer, expressed as the G′ (Pa) value obtained from a dynamic rheological measurement, correlates with bread-making quality (Pritchard, 1993). Several studies have confi rmed the importance of GMP in assessing wheat quality and predicting dough properties (Moonen et al, 1986;Sapirstein and Suchy, 1999;Kelf kens and Lichtendonk, 2000). Our regression analysis (Table 8) indicated that the polymerization index of glutenin and the GMP particle size were positively correlated with dough stability times and loaf volume.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous reports have agreed that GMP quantity is an indicator of wheat fl our quality (Weegels et al, 1996) and that the rigidity of the GMP gel layer, expressed as the G′ (Pa) value obtained from a dynamic rheological measurement, correlates with bread-making quality (Pritchard, 1993). Several studies have confi rmed the importance of GMP in assessing wheat quality and predicting dough properties (Moonen et al, 1986;Sapirstein and Suchy, 1999;Kelf kens and Lichtendonk, 2000). Our regression analysis (Table 8) indicated that the polymerization index of glutenin and the GMP particle size were positively correlated with dough stability times and loaf volume.…”
Section: Discussionmentioning
confidence: 99%
“…Higher SDS sedimentation volumes in a dry condition were due to the increased grain protein content. Variations of flour quality in the winter cultivar were related to the changes of protein composition under drought stress during grain filling (Gooding et al, 2003; Saint Pierre et al, 2008). Postanthesis water deficit may reduce the duration of storage protein accumulation rather than change the rate of accumulation of gliadins and glutenins in both spring and winter wheat cultivars (Panozzo et al, 2001; Triboi et al, 2003).…”
mentioning
confidence: 99%
“…Table 6.2 to Table 6.4. The loaf volumes of these three classified flours are reported as CWES > CWRS > SWS (Sapirstein and Suchy, 1999;Zghal et al, 2001). Thus, the density and ultrasonic properties of soluble crude gliadins in acidic solutions seem not to be related to the baking suitability of source flours but to the protein contents of the acidic soluble crude gliadins, as well as the protein contents of the source flours.…”
Section: Density and Ultrasound Resultsmentioning
confidence: 90%
“…岩瀬 祥一 * † , 三浦 靖 ** , 小林 昭一 ** (原稿受理:2005年11月2日) [2][3][4] , 混捏時の 攪拌子の回転軸に掛かるトルクを測定するミキソグラフ [5][6][7] , 生地の伸展性を評価するエクステンシグラフ 8,9) などが従来 から用いられてきた.しかし,これらの試験機は,その測定 値が装置固有のものであるばかりでなく,パン生地の力学的 挙動を詳細に解析するためには十分な情報を与えず,パン生 地の工程管理に直接に測定値を用いるのには不十分であっ た. 10) 近年では,微小な正弦応力または正弦ひずみを種々の 周波数で試料に負荷し,ひずみまたは応力を測定する動的粘 弾性測定が多く用いられるようになった. [11][12][13] また,力学特 性を測定する以外にも生地の膨張力や二酸化炭素ガス発生 量を測定する方法などもある. 14,15) さらに,電磁気学的特性 である誘電率を計測することで,ガス発生量を測定したり 16) , パン生地の水分含量などの配合条件とガラス転移温度の変 化との関連性 17) を検討するなど,誘電特性を食品の計測に利 用する動きがある. 18) しかし,混捏や発酵の操作終点の判断 をいまだに目視で行うという伝統的あるいは職人的な技法 の占める割合が依然として大きい.また,多くの試験機が開 発され,そして数多くの理化学的測定が行われているにもか かわらず,小麦粉生地が複雑な多成分の不均一混合系である ために,小麦粉製品の生地物性と製品特性との関連性は十分 に解明されていない.最近では,タンパク質-ラウリル硫酸ナ トリウム(SDS)沈降法により食パンのローフ体積を予測す ること 19,20) や,ミキソグラフを用いて食パンのローフ体積を 予測する手法 21,22) が報告されている.ところが,SDS沈降法 は測定時間が長く,しかも熟練が必要であるために誰しもが 一定の値を取得しにくい.また,パン生地のミキソグラムと ローフ体積との決定係数 (R 2 = 0.51または0.65) が低かったり, 決定係数が高い場合は重回帰分析に用いる変数の独立性に ついて検討していない場合が多々見られた. 23 食パンの原材料には,一等強力小麦粉( 「イーグル」 ,Lot. 020327AE6,日本製粉㈱) ,食塩( 「塩」 , 塩事業センター) , グラニュー糖( 「テーブルシュガー」 ,日新製糖㈱) ,ショート ニング( 「ナチュラル・ショートニング」 ,月島食品工業㈱) , 脱脂粉乳(「ローヒート」,森永乳業㈱),ドライイースト ( 「saf-instant」 , S. I. Lesaffre社) , イースト ( 「Cオリエンタルフー ド」 ,組成:塩化アンモニウム20.0 (%, w/w),硫酸カルシウム20.0 (%, w/w),炭酸カルシウム10.0 (%, w/w),L-シスチン2.0 (%, w/w), α-アミラーゼ1.0 (%, w/w),プロテアーゼ1.0 (%, w/w),L-アス コルビン酸0.6 (%, w/w),その他に小麦粉,トウモロコシデン プン,NaCl,麦芽粉末が45 (%, w/w),オリエンタル酵母工業 ㈱) ,脱塩水を用いた.試料の被覆剤にはn-ヘキサデカン(特 級,和光純薬工業㈱) ,比重測定での媒体にはn-ヘキサン(一 級,和光純薬工業㈱)をそれぞれ用いた. 2次発酵開始時に9.8 %, (w/w)であったパン生地のマルトー ス含量は,2次発酵35分後または50分後に9.4 %, (w/w),そし て2次発酵95分後には7.7 %, (w/w)にまで減少した (Table V) . よって,マルトース発酵は2次発酵35∼50分間で開始したと考 えられる.また,小麦粉内在のβ -アミラーゼが至適pH 5.2 43) であることから,2次発酵35分後のパン生地(pH 5.17)と 50分後 (pH 5.06)のパン生地ではマルトース発酵によりマル トースが消費されるもののマルトースが生成されるために パン生地中のマルトース含量が減少しなかったのではない かと考えられる.一方,2次発酵時間が65分間を超えるとパ ン生地のマルトース含量が急激に減少したのは,小麦粉内 在の α-アミラーゼの至適pHが5.5 43) であることから,pH 4.95 Table V.…”
Section: 次発酵条件を変化させたパン生地の物性と製パン特性との関連性unclassified